2006
DOI: 10.1002/anie.200601025
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Conjugate Addition of Malonates to α,β‐Unsaturated Aldehydes: Asymmetric Formal Synthesis of (−)‐Paroxetine, Chiral Lactams, and Lactones

Abstract: In addition: The scope of the title reaction is demonstrated by the synthesis of chiral lactones and lactams. The latter class of compounds is very important for the preparation of the pharmaceutical compounds such as (−)‐paroxetine and (+)‐femoxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(95 citation statements)
references
References 62 publications
2
91
0
2
Order By: Relevance
“…[16] }. Hence, the reactions with catalysts (S)-8 and (S)-9 give access to (2R,3R)-2-formylcyclopropanes 3.…”
mentioning
confidence: 97%
“…[16] }. Hence, the reactions with catalysts (S)-8 and (S)-9 give access to (2R,3R)-2-formylcyclopropanes 3.…”
mentioning
confidence: 97%
“…26,27 When these conditions were applied to α,ß-unsaturated aldehydes, complex mixtures of peroxides were observed that could not be separated. We expected the formation of dieneamines, as described in the work by Jørgensen et al 28,29 Obviously, we were not able to trap these dienes with singlet oxygen. Thus, the reaction conditions were modified and the photooxygenation was designed as a delayed step.…”
Section: Resultsmentioning
confidence: 85%
“…The enantioselectivity achieved in the catalytic cyclopropanation step was not affected by the ring-opening step. Moreover, the alcohol used in the ring-opening step can be readily changed and b-malonate esters are valuable chiral syn- [29] ). Hence, the reactions with catalysts (S)-9 and (S)-10 give access to (2R,3R)-2-formyl-cyclopropanes 3.…”
Section: Solvent and Base Screenmentioning
confidence: 99%
“…(R)-1,1-diethyl 3-ethyl 2-phenylpropane-1,1,3-tricarboxylate 18 a: [32] [a] (R)-1,1-diethyl 3-methyl 2-phenylpropane-1,1,3-tricarboxylate 18 b: [29] [a] To a stirred solution of (S)-11 (16 mg, 20 mol %) in CHCl 3 (1 mL) at 4 8C, was added aldehyde 1 h (0.3 mmol), BrCHA C H T U N G T R E N N U N G (CO 2 Et) 2 2 a (0.25 mmol), NEt 3 (0.25 mmol) and MeOH (30 mL, 3.0 equiv). The reaction was vigorously stirred at 4 8C for 6 h. To this mixture was added DIPEA (40 mol %) and thiazolium precatalyst 17 (20 mol %).…”
mentioning
confidence: 99%